iPod & iTunes visual quick tips - Shoup, Kate, 1972-; Safari eBooks (Hoboken, N.J. : Wiley Pub., 2007)
"Would you like to discover the best ways to find cool stuff on iTunes, download it all to your iPod, and get the very most out of both these hot technologies from Apple? Then this Visual Quick Tips book is for you. This book will increase your productivity by providing you with shortcuts, tricks, and tips to help you work smarter and faster. Learn how to smoothly integrate iTunes with your iPod, manage your iTunes library, and use your iPod for more than music"--Resource description page.
Description based on print version record.
Includes index.
Keywords: iPod (Digital music player); iTunes; Electronic books